Regional patterns of wild animal hunting in African tropical forests - (:unkn) unknown (My University, 2025)
Wildlife contributes to the diets, livelihoods and socio-cultural activities of people worldwide; however, unsustainable hunting is a major pressure on wildlife. Regional assessments of the factors associated with hunting offtakes are needed to understand the scale and patterns of wildlife exploitation relevant for policy. We synthesized 83 studies across West and Central Africa to identify the factors associated with variation in offtake. Our models suggest that offtake per hunter per day is greater for hunters who sell a greater proportion of their offtake; among non-hunter-gatherers; and in areas that have better forest condition, are closer to protected areas and are less accessible from towns. We present evidence that trade and gun hunting have increased since 1991 and that areas more accessible from towns and with worse forest condition may be depleted of larger-bodied wildlife. Given the complex factors associated with regional hunting patterns, context-specific hunting management is key to achieving a sustainable future.
Keywords: African Research